"Suwung": Pola penyelesaian masalah Kaum Sufi Suku Jawa di Kota Malang - Setiyowati, Ninik (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology, 2016)
â€œSuwungâ€ is a Javanesse term that describes an empty condition which has no form and is abstract. It implies emptiness with nuances of perfect self-control and true self-awareness with regard to divinity. Suwung, to the Sufi, is a spiritual experience called peak experience. Maslow defined peak experience as a condition when a person is feeling out of him-/herself mentally (Davis, 2003). Through this Suwung concept, humans can consciously solve the problems faced in life more wisely. Subject for the present research was grouped into three categories: (1) Sufis who have not met the basic needs (2) Sufis who meet the basic needs with struggle, (3) Sufis who meet the basic needs easily. The method used is the snowball sampling. Triangulation by a significant other was used for validation. The research method was qualitative phenomenology and utilizes symbolic interactionist analysis. As for the procedure, researchers conducted in-depth interviews to find the saturation values. The results of this study shows that the three groups of subjects were able to receive a problem with how to free themselves and essentially accepted the Lord in any condition. Narimo and gratitude circumstances be the basis for solving all subjects. In addition to that equation, there are three distinct patterns of thinking of a group of research subjects in solving a problem. First, humans solve problems encountered with resignation. Second, they resolve the problem by way of compromising with the facts. Third, they resolve the problem through the search for meaning of life.